Product Quality and Purchase Decisions in Skincare: The Mediating Role of Repurchase Intention and the Moderating Role of Customer Reviews - Aisyah, Nisa; Ningtyas, Alisya Sabrina; Dewi, Putri Shakira; Ezyah, Eazy (Lentera Ilmu Nusantara, 2025)
The rapid growth of the global skincare industry has intensified competition among brands to capture consumer attention, primarily through product quality offerings. This study aims to examine the effect of product quality on purchase decisions in the skincare sector, with repurchase intention as a mediating variable and customer review as a moderating variable. A quantitative explanatory approach was employed, involving 228 active skincare product users who responded to an online questionnaire. Data were analyzed using Structural Equation Modelling based on Partial Least Squares (SEM-PLS). The results reveal that product quality significantly influences both purchase decisions and repurchase intention. Furthermore, repurchase intention positively mediates the relationship between product quality and purchase decisions. On the other hand, customer reviews were found to have no significant direct effect on purchase decisions and did not moderate the relationship between product quality and purchase decisions. These findings suggest that consumers rely more on personal experience and perceived product quality rather than digital reviews. The study highlights the importance for companies to focus on product innovation and customer satisfaction to enhance repurchase behavior. Future research is recommended to involve potential consumers to broaden the understanding of purchasing behavior in the skincare market, and to explore how digital platforms might interact with consumer trust and technology acceptance in shaping long-term loyalty.